Characteristics of DNA Barcodes from Three Thrixspermum Orchids Based on ITS2 Regions - Rohimah, Siti; Ratnasari, Tri; Su’udi, Mukhamad (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2020)
Thrixspermum (T.) is one of the genus in Orchidaceae that has small flowers. Among species in this genus has a high homology and also has many synonyms. Identification using morphological characters can be constrained since Thrixspermum flowering time occurs in a very short period. This study aimed to conduct molecular-based identification of Thrixspermum orchids using DNA barcoding. This method applied molecular-based species identification technique using DNA sequences from genomic fragments that are considered fast, accurate, and consistent. The molecular markers used were Internal Transcribed Spacer 2 (ITS2), while the samples used were T. centipeda, T. lucidum, and T. angustifolium. BLAST results show that T. centipeda has a close relationship with T. centipeda from Malaysia (KX679332) with 99.79% percent identity, T. lucidum has a high homology with T. linusii (KX679333; 97.30%), while T. angustifolium has a high homology with T. triangulare (KX679348; 99.38%). There is a unique sequence that only T. lucidum and T. angustifolium have that distinguishes the two from other species. ITS2 can be recommended as a molecular marker for determining the Thrixspermum orchid barcode. The benefit obtained from this research is the DNA barcode sequences (ITS2) of Thrixspermum orchids would be very useful to enrich the plant barcodes database for further molecular taxonomy and biodiversity of orchid.Â